Management Practices of Family-Owned Businesses in Santiago City, Philippines - Luz U. Porlucas; Von P. Gabayan Jr. (American Journal of Economics and Business Management, 2023)
Family-owned businesses are one of the oldest forms of business organization. The dominance of family-owned businesses in the economies of the world dates back many years, which was why it was described as the oldest and most common form of business organization. appraised the pre-industrial revolution and first industrial revolution era, which family-owned businesses dominated, and concluded that up to this modern age, family-owned businesses still act as the backbone of most of the new and old industrialized economies around the world. Thus, this study assesses the Management practices of family-owned businesses in Santiago City in terms of Culture and Governance, Communication, Strategic Planning, Succession Planning, Leadership. A total of fifty-six (56) family-owned business owners were selected using criterion sampling. The researcher utilized quantitative methods of research using descriptive quantitative research methods to attain the objectives. The instrument used in this study was a research-made questionnaire that was distributed to the chosen family-owned business owners at their respective locations. The findings of this study revealed that the perceptions of management practices of family-owned businesses are strongly agreed with the management practices of family-owned business owners in Santiago City in terms of Culture and Governance, Communication and Trust, Strategic Planning, Succession Planning and Leadership. Moreover, the problems encountered by the owners when managing a family-owned business in Santiago City are mostly involved in Money/Income followed by Customer/Employees and the least encountered problem is Family Concerns.